THE STRUGGLE OF THE COMMUNITY OF SEDULUR SIKEP FOR ITS IDENTITY IN PATI REGENCY, CENTRAL JAVA - Endrayadi, Eko Crys (E-Journal of Cultural Studies, 2013)
This study was intended to reveal the phenomenon of the struggle of the community of Sedulur Sikep in Pati Regency, Central Java Province for its identity with the approach of cultural studies. The problems of the study can be formulated as follows (1) what was the struggle for the identity of the community of Sedulur Sikep like?; (2) what caused the struggle for the identity of the community of Sedulur Sikep to appear?; (3) what was the meaning of the struggle for the identity of the community of Sedulur Sikep to its existence. This study is a qualitative one with the researcher as the main instrument supported by an interview guide. The data were collected using the techniques of in-depth interview, observation, and documentary study. After the data were analyzed, the data were descriptively and narratively presented.  The results of the study showed that the current identity of the community of Sedulur Sikep was the result of a dialogic discourse between the community of Sedulur Sikep and the non-Sedulur Sikep communities. Based on the description above, it was found that the struggle made by the community of Sedulur Sikep for its identity was reflected in various forms of its daily life. The factors contributing to the struggle for the identity of the community of Sedelur Sikep were economic, political, social and cultural factors. The botoh Sedulur Sikep that was used as a model also contributed to it. The struggle for the identity of the community of Sedulur Sikep successfully deconstructed the old meaning and revealed the new meaning.
Keywords: struggle for identity, community of Sedulur Sikep, subaltern